Kazenskopravni vidiki plagiata - Jenull, Hinko (Podjetje in delo, 2013)
Within a wider topic of legal and ethical aspects of plagiarism the article discusses criminal protection of author's moral rights against infringements of the right to recognition of authorship and the right to integrity of work. On the level of normative regulation in the Slovenian Penal Code, the statutory definition of a criminal offence, modes of committing a criminal offence, forms of culpability and sanctions in the scope of criminal offence Violation of Moral Rights (Article 147 of the Penal Code) are described in detail. A short description is dedicated also to the criminal offence Violation of Substantive Copyright (Article 184 of the Penal Code). Procedural aspects for the possibility of prosecution of legal persons and the basis for establishing the responsibility for misdemeanors regarding the infringement of copyrights are described separately.
Keywords: avtorske pravice; avtorsko pravo; intelektualna lastnina; kršenje; plagiatorstvo; pravno varstvo